'Stop calling it graffiti': The visual rhetoric of contamination, consumption and colonization. (September 2019) - Landry, Deborah
Municipal graffiti abatement approaches in North America have shaped the stories we tell ourselves about ourselves upon these city walls. This article examines how the City of Ottawa (Canada) manages graffiti and murals. In doing so, I demonstrate how those management practices connect to longstanding tensions about unauthorized markings in public places and the criminalization of style. Drawing from extensive ongoing ethnographic research on graffiti and the moral and legal regulation of urban performances, I reveal the aesthetics of security which fosters a visual logic of so-called 'crime prevention, ' state-sanctioned redactions and racialized dispossession of phrasing and text. To close, I consider how urban art regimes are implicated in the colonizing of public spaces, while also considering the liberating possibilities of graffiti.